Livestock Fence Construction - Reyna Speckmann; Jeff Steele (EDIS)
AN230, a 5-page illustrated fact sheet by Reyna Speckmann and Jeff Steele, describes the materials and assembly guides that are standard operating procedures practiced at the UF/IFAS Range Cattle Research and Education Center in Ona, FL. Published by the UF Department of Animal Sciences, November 2009.